AUTOIMMUNE RHEUMATIC DISEASES: RESULTS AND PROSPECTS FOR RESEARCHES - E. L. Nasonov; E. N. Aleksandrova; A. A. Novikov (Научно-практическая ревматология, 2015)
According to the present-day views, autoimmunity is a complex pathological process, the essence of which is intolerance and hence a pathological immune response to intrinsic tissue components (autoantigens), which underlies the pathogenesis of a broad spectrum of human autoimmune diseases. Recently, diverse immune disorders underlying autoimmune rheumatic diseases (ARD) and syndromes have been revealed; an association has been found between the development of ARD and autoinflammatory diseases and syndromes; a classification of human immunoinflammatory diseases has been elaborated. The paper considers the results of the authors’ investigations of ARD treatment with innovative biologics, the pathogenetic mechanisms and diagnosis of ARD, by conducting immunological and molecular biological studies of a wide range of molecular and cellular biomarkers (autoantibodies, acute phase proteins, cytokines, chemokines, vascular endothelial activation markers, complement system components, lymphocyte subpopulations, bone and cartilage tissue metabolic products, genetic, epigenetic, transcriptomic markers), and approaches to personalized treatment of ARD.